Efektifitas Fungsi Hukum (UU No. 1/1974 dan KHI) Sebagai Sosial Engineering Terhadap Pernikahan di Bawah Tangan - Mardiantari, Ani (CV. Creative Tugu Pena, 2024)
Marriage plays a very important role in creating a good social culture, therefore, legally speaking, Law no. 1/1974 Article 2 paragraph 2 explains that every marriage must be registered according to applicable legislation. The existence of these regulations regarding marriage registration should make it easier for the public to handle the administration of legalizing marriages. However, in Bumi Nabung Village, Central Lampung, there are still illegal marriages, even though the number is not large, this proves that the effectiveness of the legal function as social engineering is not yet optimal. The purpose of this research is to determine the effectiveness of the function of law (UU No. 1/1974 Article 2 Paragraph 2 Jo KHI Article 5 Paragraph 1) as a social technique for underhanded marriages in Bumi Nabung Village. This research is field research using qualitative methods and normative juridical and empirical juridical approaches. The primary data source in this research is the place and the husband and wife who married privately at Drsa Bumi Nabung. The results of this research still found that there were illegal marriages in Bumi Nabung Village, but the number was approximately only 20 married couples out of the total number of families, so it can be concluded that the function of law as social engineering is effective